2012
DOI: 10.1136/neurintsurg-2011-010248
|View full text |Cite
|
Sign up to set email alerts
|

Invasive interventional management of post-hemorrhagic cerebral vasospasm in patients with aneurysmal subarachnoid hemorrhage

Abstract: Current clinical practice standards are addressed for the invasive interventional management of post-hemorrhagic cerebral vasospasm (PHCV) in patients with aneurysmal subarachnoid hemorrhage. The conclusions, based on an assessment by the Standards Committee of the Society of Neurointerventional Surgery, included a critical review of the literature using guidelines for evidence based medicine proposed by the Stroke Council of the American Heart Association and the University of Oxford, Centre for Evidence Base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 64 publications
0
35
0
1
Order By: Relevance
“…Although it is recognised that elevated intracranial pressure, systemic hypotension and seizures may complicate infusion of either agent [37], this was not 46 Inagawa/CT [13] Mild-moderate (< 50%) 5 Severe (> 50%) 63 Weidauer/MR [14] Mild (10-33%) 3 Moderate (34-66%) 16 Severe (> 66%) 81 Present study/CT Severe (> 66%) 18 encountered in this series. Recognised complications of TBA include vessel dissection, perforation, occlusion and rupture, reperfusion haemorrhage, infarction and clip displacement [38].…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Although it is recognised that elevated intracranial pressure, systemic hypotension and seizures may complicate infusion of either agent [37], this was not 46 Inagawa/CT [13] Mild-moderate (< 50%) 5 Severe (> 50%) 63 Weidauer/MR [14] Mild (10-33%) 3 Moderate (34-66%) 16 Severe (> 66%) 81 Present study/CT Severe (> 66%) 18 encountered in this series. Recognised complications of TBA include vessel dissection, perforation, occlusion and rupture, reperfusion haemorrhage, infarction and clip displacement [38].…”
Section: Discussionmentioning
confidence: 62%
“…Recognised complications of TBA include vessel dissection, perforation, occlusion and rupture, reperfusion haemorrhage, infarction and clip displacement [38]. Older series had documented rupture rates as high as 4-5% but with modern compliant balloons the rupture rate is probably in the order of 1% [34,37]. Retrospective analyses at hospital and nationwide levels have suggested that institutions that offer endovascular treatment for vasospasm may have lower rates of unfavourable outcome [39,40].…”
Section: Discussionmentioning
confidence: 97%
“…242 Transluminal balloon angioplasty and intra-arterial vasodilator therapy should be considered for the management of symptomatic vasospasm. 70,71,243 Prophylactic intra-arterial vasodilator therapy is not indicated before development of angiographic vasospasm. 70,71 Other Pharmacological Agents for the Management of DCI The Magnesium in Aneurysmal Subarachnoid Hemorrhage (MASH) trial, a phase II RCT found that IV magnesium, an arteriolar dilator, improved neurological outcome.…”
Section: Biomarkers For DCImentioning
confidence: 99%
“…Although, to our knowledge, there is no prospective clinical trial data to support its use, balloon angioplasty has become a cornerstone of treatment at the majority of centers for focal large vessel vasospasm that is non-responsive to intra-arterial dilation or traditional medical therapy [4,5]. Radiographic improvement after balloon angioplasty is quite impressive but there are conflicting reports regarding use and timing of this treatment modality to augment medical therapy for moderate vasospasm [5][6][7]. In severe medically refractory vasospasm, endovascular treatment, including balloon angioplasty, can be essential in preventing delayed ischemic complications of vasospasm [8].…”
Section: Introductionmentioning
confidence: 97%